The efficacy of total hip arthroplasty in patients with systemic lupus erythematosus: a systematic review and meta-analysis - Jun Lu; Jiangting Yu; Xiaoping Wang; Tingting Hua (Journal of Orthopaedic Surgery and Research)
Abstract Introduction Systemic lupus erythematosus (SLE) can lead to avascular necrosis (AVN) of the femoral head, often requiring total hip arthroplasty (THA). However, outcomes and complications of THA in SLE patients remain unclear. This study aims to analyze the differences in clinical outcomes and complications between SLE and non-SLE patients undergoing THA. Methods This study adhered to the PRISMA guidelines and was registered in PROSPERO (CRD42024564792). Literature was retrieved from the Cochrane Library, Web of Science, PubMed, and Embase databases, supplemented by manual searches of relevant references. Studies meeting specific diagnostic criteria were included, with eligible study types comprising case-control and cohort studies. The intervention of interest was THA surgery, and primary outcome measures included adverse events and clinical outcomes. Risk of bias was assessed using the Cochrane Risk of Bias tool for randomized trials and the Newcastle-Ottawa Scale for observational studies. Statistical analyses were performed using RevMan 5.4 software. Dichotomous variables were analyzed using relative risk (RR), while continuous variables were assessed using the mean difference (MD) or standardized mean difference (SMD), both with 95% confidence intervals for effect size estimation. Heterogeneity was assessed via the X² test and I² statistic, with P ≤ 0.05 considered statistically significant. Results No significant difference in Harris Hip Scores (HHS) (MD= -0.69, 95% CI: -2.11 to 0.73, I²=0%, P = 0.34) was observed between SLE and non-SLE patients. However, compared to non-SLE patients, SLE patients had higher risks of prosthesis dislocation (RR = 2.44, 95% CI: 1.74 to 3.42, I²=52%, P<0.01), wound infection (RR = 2.30, 95% CI: 1.87 to 2.83, I²=0%, P<0.01), and blood transfusion (RR = 2.50, 95% CI: 2.14 to 2.92, I²=0%, P<0.01), as well as longer hospital stays (MD = 1.64, 95% CI: 1.44 to 1.64, I²=100%, P<0.01). Discussion In conclusion, although SLE patients show similar improvements in hip function postoperatively compared to non-SLE patients, they face a significantly higher risk of complications, including prosthetic dislocation, blood transfusion requirements, DVT, and wound infections. These patients also experience longer hospital stays and slower recovery, likely due to their underlying health conditions and preoperative treatments. Personalized management strategies and risk assessments are crucial to minimize complications and optimize recovery outcomes for SLE patients undergoing THA. However, the included studies exhibit significant heterogeneity, including variations in prosthesis types, fixation methods, sample sizes, and study designs, which may introduce potential bias and affect the generalizability of the findings. Further high-quality research is needed to address these issues.